2016
DOI: 10.1140/epjp/i2016-16320-3
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional dispersion phenomena in terms of fractional media

Abstract: Abstract. It is well know that structured solids present dispersive behaviour which cannot be captured by the classical continuum mechanics theories. A canonical problem in which this can be seen is the wave propagation in the Born-Von Karman lattice. In this paper the dispersive effects in a 1D structured solid is analysed using the Fractional Continuum Mechanics (FCM) approach previously proposed by Sumelka (2013). The formulation uses the Riesz-Caputo (RC) fractional derivative and introduces two phenomenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The foundations for dynamic equilibrium for 1D sFCM body were formulated for a constant length scale in [34,35]. Subsequently, after introducing variable length scale concept to sFCM in [36], an extension of [34,35] was proposed in [32].…”
Section: Dynamic Equilibrium For 1d Sfcm Body Including Spatially Var...mentioning
confidence: 99%
“…The foundations for dynamic equilibrium for 1D sFCM body were formulated for a constant length scale in [34,35]. Subsequently, after introducing variable length scale concept to sFCM in [36], an extension of [34,35] was proposed in [32].…”
Section: Dynamic Equilibrium For 1d Sfcm Body Including Spatially Var...mentioning
confidence: 99%
“…It is important that this concept was validated with experimental result in Sumelka et al (2015a), where the s-FCM concept was used to mimic the behaviour of micro-beams made of the polymer SU-8 (where strong scale effect was observed), and furthermore, in Sumelka et al (2016) it was presented that s-FCM can correctly mimic the Born-Von Karman (BK) lattice (discrete system). This result are crucial for correctness of physical interpretation of the results obtained below.…”
Section: D Inhomogeneous Fractional Elasticitymentioning
confidence: 99%
“…Eringen showed that the dispersion cure based on the non-local theory is in good agreement with Born–von-Kármán model of the lattice dynamics. More recently, Challamel et al (2013) by generalizing the Eringen non-local theory in terms of fractional calculus has provided a general approximation for the integral form of the constitutive relation which contains the integer and the non-integer orders of the stress gradient (Sumelka et al , 2016). They showed that the optimized fractional model shows perfect matching with Born–von-Kármánmodel of the lattice dynamics and is better than the Eringen model.…”
Section: Introductionmentioning
confidence: 99%